Memoria dislocata. Svetlana Boym, Marija Stepanova e la poetica nella Russia post-sovietica (Itinera, 2024)
Post-Soviet literature and theoretical reflection constitute an elective place for the elaboration of memory; the reflection of Svetlana Boym (starting exemplary from her work on Nabokov) and the poetic work of Marija Stepanova between poetry, prose and essays are the subject of these notes, which pay particular attention to the dislocation of memory as a reactivation of history in the double emergency of condition specific to the post-memory generation and the erasure of history by the Putin regime.